Application of a Deterministic Distributed Hydrological Model for Estimating Impact of Climate Change on Water Resources in Côte d’Ivoire Using RCP 4.5 and RCP 8.5 Scenarios: Case of the Aghien Lagoon - N’Dri, Wa Kouakou Charles; Pistre, Séverin; Jourda, Jean Patrice; Kouamé, Kan Jean (International Research in Environment, Geography and Earth Science Vol. 9, 2021)
This work aims to evaluate the impact of climate change on the quantitative availability of the Aghien lagoon located in the north of the Abidjan district in Côte d'Ivoire. In first step, the semi-distributed SWAT (Soil and Water Assessment Tools) based physical model [1] was calibrated and validated at the monthly time step over the period 1960-1981, in the Mé watershed where flow rates data are available. SWAT was then applied on the watershed of the lagoon of Aghien which is ungauged but for which the challenges are considerable for the drinking water supply of the Abidjanese population. In a second step, the gross outputs (precipitation, temperatures) of six climate models of the CORDEX-Africa project under the "Representative Concentration Pathways" (RCP 4.5 and RCP 8.5) scenarios were corrected using the delta method. These corrected outputs were used at the SWAT model input to project the impact of climate change on the flow of the Aghien lagoon for horizons 2040 (2035-2056), 2060 (2057-2078) and 2080 (2079-2100). The projections made on these different horizons were compared with the simulated flow over the period 1960-1981. The results show a sensible decrease in the annual flow of the Aghien lagoon compared to the reference period (1960-1981). Under the medium assumption (RCP 4.5), the models predict a decrease in the annual discharge almost 10% on average. Under the pessimistic hypothesis (RCP 8.5), the average annual discharge should decrease by more than 17%. On a monthly basis, flows in August and September would increase by more than 80% and those in October and November would increase by more than 20% in both RCP scenarios.